Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada Suncity Festival Madiun - Pernanda Wulandari (Jurnal Ilmu Manajemen, 2022)
A comfortable and supportive work environment at the company needs to be maintained because a suitable compensation and supportive work environment will create good job satisfaction and increase employee productivity to reach the company goal. This research aims to study the effect of Compensation and Work Environment on employees' job satisfaction. This study uses data analysis techniques and multiple linear regression analysis SPSS version 25 software program. Data were obtained from the distribution of questionnaires with uses sample amount of 60 employees. The statistical test result of this study explains that compensation hasn't a significant effect on employee job satisfaction. The work environment has a positive and significant impact on job satisfaction. Simultaneously, the compensation and work environment positively and significantly affect employee job satisfaction. The result shows that the company should give more attention to the compensation given to their employees and more attention to providing a fair compensation system for their needs and achievements.